Assessing mechanical characteristics of typical support system being used in thin seam coal mining of Pakistan. (25th March 2023) - Shahzad, Muhammad; Majeed, Yasir; Emad, Muhammad Zaka; Arshad, Mahmood; Goraya, Rangzeb; Akram, Muhammad
In Pakistan, most of the coal mines located in the Salt Range utilise wood or timber as the main component of support system comprising of cribs, two-piece and three-piece sets. The commonly used variety of timber by the coal mining industry of Pakistan includes Acacia nilotica (Linn.), delile and eucalyptus. This research work is focused on the strength characteristics of bending and compression members of acacia wood being used as support components in underground coal mines. Easy to use equations for the prediction of flexural strength, uniaxial compressive strength (UCS) of wood parallel and perpendicular to grain from density are also proposed. Efforts were made to enhance the bending strength of wooden beams of acacia which showed an increase of 23.45% through applying reinforcement. Moreover, full column crib strength was determined to evaluate its roof supporting capacity. Besides this an alternate compression member to acacia wood support has also been evaluated and introduced in the form of brick support.